Functional requirements for subject authority data (FRSAD) and collaborative metadata models in islamic finance for interoperable bibliographic databases among libraries - Naizura Abd Rashid (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2016)
Knowledge of Islamic finance is evolving, resulting in the numerous bibliographic databases on Islamic finance have been developed in silos. Due to the growing nature of this knowledge, there is a need for its subject terms to be understood by users. Therefore, it is a need to increase the subject vocabulary control for this knowledge in bibliographic databases. The development of most current bibliographic databases such as library online catalogues use the top-down approach where end users are not involved, resulting in their metadata not adequately meeting the pragmatic needs of the users. The objectives of the study were to identify elements for metadata collaboration among bibliographic databases, investigate compatibility between system and user metadata elements, and ascertain the practicality of Islamic financial terms as the subject vocabulary control tool. The system metadata were gained from ten libraries in Malaysia with considerable size of Islamic finance resources, and user metadata were obtained from 301 respondents from an Islamic Finance domain. The mixed -method sequential exploratory design was used in identifying elements created in the selected libraries' databases, metadata preferred by users and users' opinions on the usage of Islamic financial terms as subject vocabulary in information searching. The study applied a Collaborative Metadata Approach and the Functional Requirements for Subject Authority Data (FRSAD) Conceptual Modeling of Aboutness, a derivative from basic relationships defined in the Functional Requirements for Bibliographic Records (FRBR) model. The findings identified 'Author', 'Title' and 'Subject' as common metadata elements among bibliographic databases. However, inconsistencies were discovered on subject headings used and class numbers created for similar books. 'Title' and 'Subject' were identified as user preferred metadata elements and these elements are currently available in the webOPAC of selected libraries. The analysis indicated that the MARC fields were not sufficient created to describe the requirements on FRSAD entities for the aboutness. The study also found limited Islamic Financial Terms (IFT) was coded as the subject terms in the MARC records. Users demonstrated the ability, familiarity and positive perceptions on IFT as keywords in subject search, despite non-standardisation of spellings for identical IFT. This study suggests for the deployment of IFT as the subject vocabulary control tool, and recommends for cataloguing collaboration process in developing guidelines for system metadata consistencies and a reference standard for IFT. The collaboration among the systems metadata fosters content-sharing, resource discovery and cross-searching.